Using narrative writing to enhance healing during and after global health crises - Bird, Jennifer Lynne (Information Science Reference, 2022)
"This authored book explains how there is a growing body of evidence that suggests that patients who actively write about their health conditions are able to process worries, concerns, frustrations and fears and gradually convert negative thoughts into more positive thoughts and an overall more positive attitude toward their situation"--